HE IMPACTS OF RACISM ON ELLA DOWNEY’S PSYCHOLOGICAL CONDITION IN EUGENE O’NEILL’S “ALL GOD’S CHILLUN GOT WINGS” - IKHFADZNI, NURIL (Jurnal Ilmiah Mahasiswa FIB, 2013)
Keywords:  Racism, Psychological Disturbance, Post Traumatic Stress Disorder, Psychosis   America is known for its long history dealing with  racism. Through categorization, many forms of racism such as stereotype, prejudice and discrimination are widespread and done by the majorities toward minorities. White Americans are the example of the majority group that is seen as the agent of racism that often practices racial actions toward the minorities such as Black Americans. Unfortunately, racism gives impacts on both White Americans and also Black Americans. “All God’s Chillun Got Wings” is a drama that elevates this phenomenon. This study focuses on how racism gives impacts on Ella Downey’s psychological condition as a White American that is seen as an agent of racism. This study employs socio-psychological approach to  discover the influence of a social construct, which is in this case is racism, and its impacts on psychological condition of Ella Downey as the agent of racism that also wife of Jim, one of a Black Americans that are seen as inferior ones in American society. This study reveals that there are significant impacts of racism on the psychological disturbances that are experienced by Ella as the agent of racism. Racism that she holds places her in many stressful conditions that make her has to endure post traumatic stress disorder (PTSD) and psychosis. These psychological disturbances are the impacts of racism which bring her to the confusion related to the way she treats Black Americans especially Jim Harris. Racism even brings her to be a violent mania